Benefit‐sharing with human participants in health research in South Africa: A call for clarity - Kamau, Claude; Prinsen, Larisse; Thaldar, Donrich (Developing world bioethics, 2025)
This study critically examines the concept of benefit‐sharing in the context of health research involving human participants in South Africa, identifying a significant gap in the precision and application of terminology. It introduces a new terminological framework designed to provide clarity and facilitate standardisation in both national and international discourse on benefit‐sharing. The analysis extends to the complex legal landscape in South Africa, highlighting the nuances of mandated, permitted, and prohibited practices of benefit‐sharing across various statutes. This reveals substantial implications for ethics committees, researchers, and participants, emphasising the need for a legal and ethical recalibration. Furthermore, the manuscript critiques South Africa's main ethics instruments for their inadequate guidance on benefit‐sharing and proposes recommendations for enhancing the Department of Health's ethics guidelines. By advocating for a coherent, legally informed approach to ethical decision‐making, the study underscores the need for integrating the proposed framework and legal insights into ethics guidelines. This comprehensive strategy aims not only to advance ethical practices within South Africa but also to contribute significantly to the global discourse on benefit‐sharing in health research.